Preserving Community Interests in Ocean Governance towards Sustainability 2nd Edition - Zou, Keyuan; Chang, Yen-Chiang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
References to community interests appear from time to time in scholarly writings in the field of international relations and international law. The concept of community interests refers to interests protected by international law binding either all or a group of states and go beyond the delimitation of a sovereign sphere of influence. In the literature, there are existing examples of research, such as in books and journal articles, that consider the various manifestations of what has been described as "community interests" in many areas regulated by international law, including natural resources, global markets, human rights, and the use of force, and observe how law has evolved from a legal system based on more or less specific consent and aimed at promoting the particular interests of states, to one that is more generally oriented towards collectively protecting common interests and values. However, this topic has not been thoroughly researched, meaning that there is a huge gap in the existing literature, particularly in the context of ocean governance and sustainability. This Special Issue attempts to fill this gap, so as to attract more studies on this important topic in academia.